2014
DOI: 10.3329/bmrcb.v39i3.20317
|View full text |Cite
|
Sign up to set email alerts
|

Auto-analyzer based screening of microcytic hypochromic ratio to differentiate thalassaemia and non thalassemic microcytosis

Abstract: DOI: http://dx.doi.org/10.3329/bmrcb.v39i3.20317 Bangladesh Med Res Counc Bull 2013; 39: 146-147

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…24 Similar results indicating Mentzer Index to be highly sensitive (90.9%) was observed by Ghafouri et al 25 A study by Kabir AL et al, however showed 96% sensitivity for M/H ratio with a predictive value of 90.4% in screening for BTT. 26 We observed that with a cut off value of 1.8 for M/H ratio, we could diagnose BTT with maximal diagnostic sensitivity but at expense of specificity.…”
Section: Discussionmentioning
confidence: 76%
“…24 Similar results indicating Mentzer Index to be highly sensitive (90.9%) was observed by Ghafouri et al 25 A study by Kabir AL et al, however showed 96% sensitivity for M/H ratio with a predictive value of 90.4% in screening for BTT. 26 We observed that with a cut off value of 1.8 for M/H ratio, we could diagnose BTT with maximal diagnostic sensitivity but at expense of specificity.…”
Section: Discussionmentioning
confidence: 76%